Evaluation Of Pedigree Goats In Wooly Goat Farming - Izatulla Yangiboyevich Eshmatov (Genius Journals, 2022)
The article provides information and feedback on the establishment of lines from the gene pool of Angor breed goats, the use of selection methods in selection activities, and goat breeding evaluation.
Keywords: Selection; Gene Pool; Angor Breed Goat; Mother Goat